High-permeability puncture-resistant membrane material, preparation method and application in rice planting

By introducing maleic anhydride and epoxy modified silicon-based mesoporous materials into PBAT, a high permeability puncture-resistant membrane material is formed, which solves the problem of insufficient permeability and puncture-resistant membrane material in the prior art, and realizes gas exchange and improve the protective effect, suitable for rice seedling cultivation.

CN119192628AActive Publication Date: 2024-12-27BAOQING NORTH RICE RES CENT +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411267590.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-27
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

In the prior art, the permeability and puncture resistance of membrane materials are insufficient, making it difficult to meet the gas exchange and protection requirements during rice seedling cultivation.

Method used

Maleic anhydride graft modified PBAT and epoxy modified silicon-based mesoporous materials are combined to form a highly permeable puncture-resistant film material through chemical bonding, improving the toughness and gas diffusion properties of the film material.

Benefits of technology

The high permeability and puncture resistance of membrane materials are achieved to ensure the normal breathing and photosynthesis of rice seedlings, while providing good insulation and protection effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192628A_ABST
    Figure CN119192628A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of plastic materials, in particular to a high-permeability puncture-resistant film material, a preparation method and application in rice planting. The membrane material takes PBAT as a base material, and the PBAT-based membrane material has the characteristics of good biodegradability, high water vapor permeability and the like; the toughening material is introduced into the PBAT, so that the toughness of the membrane material can be effectively improved, and the puncture resistance of the membrane material is further improved; the toughening material comprises an organic toughening material and an inorganic toughening material, both the organic toughening material and the inorganic toughening material are connected to polylactic acid molecules through stable chemical bonds, and the toughening effect is good; the inorganic toughening material silicon-based mesoporous material has a porous structure, has small permeation resistance to gas, is beneficial to diffusion and transmission of gas, and can improve the permeability of the membrane material. When the membrane material is applied to rice planting, temperature increasing and water retention can be achieved, and meanwhile it can be guaranteed that nutrient exchange, respiration and photosynthesis of rice seedlings are efficiently carried out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic materials, and in particular to a high-permeability puncture-resistant film material, a preparation method and application thereof in rice planting. Background Art

[0002] The growth cycle of rice is long. For rice in cold regions in the north, the sowing and seedling raising period is mostly around Qingming Festival, when the temperature is relatively low. The seedling raising process generally requires the use of a shed to effectively increase the temperature of the seedling bed and help cultivate strong seedlings. In order to seize the farming season, shorten the seedling raising time, and increase the temperature of the seedling bed, rice seedlings are raised by covering the seedling bed with molds in the shed and covering the field with film. However, during the growth of the seedlings, in order to ensure the normal respiration and photosynthesis of the seedlings, the oxygen, carbon dioxide, and water vapor content in the film needs to be kept within a certain range. Similarly, the application of film covering technology in paddy fields where straw is returned to the field will lead to untimely gas exchange during the process of accelerating straw decomposition, which can easily cause rice hydrogen sulfide poisoning or even root rot. Therefore, the permeability of the membrane material is required to be high, and the permeability of the membrane material itself is required to achieve the penetration and diffusion of oxygen, carbon dioxide, methane, and water vapor inside and outside the membrane; in addition, if the membrane material is punctured and damaged, it will affect the normal growth of the seedlings, so the membrane material is required to have good puncture resistance.

[0003] Chinese patent CN107469640B discloses a method for preparing a high gas permeability carbon membrane, which utilizes the pore structure of the carbon membrane to achieve its high gas permeability. However, it is mainly used for the separation of small molecule gases. The mechanical properties of the carbon membrane, such as strength and toughness, are far inferior to those of plastic films, and it is difficult to use it as a coating material. Chinese patent CN115558139B discloses a process for preparing an antibacterial and puncture-resistant PBAT composite film, which improves the toughness of the composite film by adding styrene-maleic anhydride copolymer and polyethersulfone, thereby improving the puncture resistance of the composite film. However, the raw material components are physically blended during the preparation process, and the dispersion uniformity and compatibility are poor, and the puncture resistance needs to be improved. In addition, the permeability of the antibacterial and puncture-resistant PBAT composite film is poor. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a high-permeability puncture-resistant membrane material and a preparation method to solve the problem in the prior art that the permeability and puncture-resistant performance of the membrane material need to be improved.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a high-permeability puncture-resistant membrane material comprises the following steps:

[0007] Step 1: adding maleic anhydride grafted modified PBAT into chloroform, stirring until dissolved, adding amino-terminated liquid nitrile rubber dropwise, reacting after the addition is complete, precipitating, filtering, washing, and drying to obtain nitrile rubber modified PBAT;

[0008] Step 2: adding the silicon-based mesoporous material to toluene, and after ultrasonic dispersion, adding γ-glycidyloxypropyltrimethoxysilane, continuing ultrasonication, reacting, and after the reaction is completed, centrifuging, purifying, and drying to obtain the epoxy-modified silicon-based mesoporous material;

[0009] The nitrile rubber modified PBAT, the epoxy modified silicon-based mesoporous material, the antioxidant and the lubricant are mixed and melted to obtain a modified PBAT melt;

[0010] Step 3: Extrude the modified PBAT melt and blow the film to obtain a high permeability and puncture-resistant film material.

[0011] Preferably, the maleic anhydride grafted modified PBAT used in step 1 is prepared by the following steps:

[0012] PBAT (copolymer of butylene adipate and butylene terephthalate), maleic anhydride, and initiator diisopropylbenzene peroxide are mixed, melted, extruded, and granulated. The melting, extrusion, and granulation process are repeated three times, and dried to obtain maleic anhydride grafted modified PBAT.

[0013] Furthermore, the mass ratio of the PBAT, maleic anhydride and initiator dicumyl peroxide is 100:(5-10):(1.5-3); and the melting temperature is 135-155°C.

[0014] Preferably, in the step 1, the mass ratio of maleic anhydride grafted modified PBAT, chloroform, and amino-terminated liquid nitrile rubber is (100.5-101.5):(1000-1200):(15-25), and the reaction conditions are reflux reaction at 50-60° C. for 2-3 hours.

[0015] Preferably, in step 2, when preparing the epoxy-modified silicon-based mesoporous material, the mass ratio of the silicon-based mesoporous material, toluene and γ-glycidyloxypropyltrimethoxysilane is (5-10):200:(2-5), and the reaction conditions are 85-95° C. for 5-10 hours.

[0016] Preferably, in the step 2, the ultrasonic dispersion is performed at a power of 300 W for 20-40 min, and the ultrasonic dispersion is performed at a power of 300 W for 5-10 min.

[0017] Preferably, in step 2, purification comprises adding toluene to the centrifugal precipitate, dispersing the precipitate by ultrasonication, centrifuging the precipitate, taking the centrifugal precipitate, and repeating the ultrasonic dispersion and centrifugal separation process six times.

[0018] Preferably, in the step 2, when preparing the modified PBAT melt, the mass ratio of nitrile rubber modified PBAT, epoxy modified silicon-based mesoporous material, antioxidant and lubricant is 100:(3-5):(0.5-1):(0.5-1), and the melting temperature is 160-170°C.

[0019] Preferably, in the step 2, the antioxidant comprises any one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, n-octadecanol β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate];

[0020] The lubricant includes any one of calcium stearate and zinc stearate.

[0021] In the step 3, the extrusion die temperature is 165-175°C.

[0022] The present invention also discloses a high-permeability puncture-resistant membrane material prepared by the above-mentioned method for preparing the high-permeability puncture-resistant membrane material.

[0023] Preferably, the high permeability puncture-resistant membrane material as described above is used in rice planting.

[0024] Furthermore, the application in rice planting includes the following specific processes: preparing ridges before flooding the fields, digging ridge furrows 20-30 cm deep every 100 cm, spraying microbial agents on the fields after flooding the fields for 3-5 days, leaving the fields for 2 days after fertilization, covering the ridges with high permeability and puncture-resistant film materials, with the film materials close to the soil surface to prevent grass growth; when transplanting rice, there are two rows of rice on each ridge, and after transplanting, the ridges and furrows are always kept with water but the film surface is dry, and microbial agents are sprayed multiple times after rice transplanting and before and after heading, and the ridges and furrows are evenly spread when applying topdressing; draining and drying the fields 15 days before harvesting, and the film materials do not need to be recycled and can be naturally degraded.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] In the present invention, PBAT is used as the matrix material. PBAT has the characteristics of both PBA and PBT, and has good mechanical properties and biodegradability. The PBAT base film material also has the characteristics of high water vapor permeability and good carbon dioxide adsorption and diffusion.

[0027] A method for preparing a high-permeability puncture-resistant membrane material comprises the following steps:

[0028] In the present invention, by introducing toughening materials into PBAT, the toughening materials include organic toughening materials of nitrile rubber and inorganic toughening materials, silicon-based mesoporous materials, which can effectively provide toughness of the membrane material, thereby improving the puncture resistance of the membrane material; in the process of introducing the toughening materials, PBAT is grafted with maleic anhydride to modify PBAT, and the maleic anhydride grafted modified PBAT first undergoes a ring-opening reaction between maleic anhydride and the amino groups on the amino-terminated liquid nitrile rubber molecules to generate carboxyl groups and amide bonds connecting PBAT and nitrile rubber to obtain nitrile rubber. Nitrile rubber modified PBAT; the pores of the silicon-based mesoporous material are modified by γ-glycidyloxypropyltrimethoxysilane, and the introduced epoxy group reacts with the carboxyl group generated by the ring-opening reaction of maleic anhydride and the imino group on the amide bond to chemically connect the silicon-based mesoporous material to the nitrile rubber modified PBAT molecule; both the organic toughening material and the inorganic toughening material are connected to the PBAT molecule by stable chemical bonds, and have good compatibility with the PBAT resin and uniform dispersion in the PBAT resin, and good toughening effect;

[0029] In addition, silicon-based mesoporous material is a porous silica material with a pore size between 2-50nm. Due to its porous structure, it is added to PBAT resin to prepare membrane material, which has low gas permeation resistance, is conducive to gas diffusion and transmission, and can effectively improve the permeability of membrane material. The membrane material is used as a rice seedling film in rice planting, which not only has a good heat preservation effect, but its high permeability can also ensure the normal respiration and photosynthesis of rice seedlings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a process flow chart for preparing the high permeability puncture-resistant membrane material of the present invention;

[0031] Figure 2 It is a bar graph of the O2 transmittance test results of the membrane materials prepared in Examples 1-6 of the present invention and Comparative Examples 1-3;

[0032] Figure 3 A bar graph showing the CO2 permeability test results of the membrane materials prepared in Examples 1-6 and Comparative Examples 1-3 of the present invention;

[0033] Figure 4 It is a bar graph showing the test results of water vapor transmission rate of the film materials prepared in Examples 1-6 of the present invention and Comparative Examples 1-3;

[0034] Figure 5 It is a bar chart showing the test results of the puncture resistance of the film materials prepared in Examples 1-6 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] A method for preparing a high-permeability puncture-resistant membrane material comprises the following steps:

[0038] Step 1: Mix PBAT, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:5:1.5, melt, extrude, and granulate at 135°C, repeat the melting, extrusion, and granulation process three times, and place in a 70°C oven to dry for 24 hours to obtain maleic anhydride grafted modified PBAT;

[0039] Step 2: Add the maleic anhydride grafted modified PBAT to chloroform, stir until dissolved, and add amino-terminated liquid nitrile rubber dropwise. The mass ratio of maleic anhydride grafted modified PBAT, chloroform, and amino-terminated liquid nitrile rubber is 100.5:1000:15. The dropwise addition time of the amino-terminated liquid nitrile rubber is 30 minutes. After the dropwise addition is completed, reflux reaction is carried out at 50°C for 3 hours. After the reaction is completed, 5 times the mass of chloroform is added for precipitation, filtration is performed, the filter cake is taken, washed three times with ethanol, and dried in a vacuum oven at 60°C for 12 hours to obtain nitrile rubber modified PBAT;

[0040] Step 3, add the silicon-based mesoporous material to toluene, ultrasonically disperse it at a power of 300 W for 20 minutes, add γ-glycidyloxypropyltrimethoxysilane, the mass ratio of silicon-based mesoporous material, toluene, and γ-glycidyloxypropyltrimethoxysilane is 5:200:2, continue ultrasonication at a power of 300 W for 5 minutes, react at a temperature of 85°C for 10 hours, centrifuge after the reaction, add toluene to the centrifugal precipitate, ultrasonically disperse it at a power of 300 W for 10 minutes, centrifuge, take the centrifugal precipitate, repeat the ultrasonic dispersion and centrifugation process six times, place it in a vacuum oven at 60°C and dry it for 12 hours to obtain the epoxy-modified silicon-based mesoporous material;

[0041] The nitrile rubber modified PBAT, epoxy modified silicon-based mesoporous material, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, and calcium stearate are mixed, and the mass ratio of the nitrile rubber modified PBAT, epoxy modified silicon-based mesoporous material, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, and calcium stearate is 100:3:0.5:0.5, and the mixture is melted at a melting temperature of 160° C. to obtain a modified PBAT melt;

[0042] Step 4: Extruding the modified PBAT melt at an extrusion die temperature of 165° C. and blowing the film to obtain a high permeability puncture-resistant film material;

[0043] The thickness of the high permeability puncture-resistant membrane material is 0.25 mm.

[0044] Example 2

[0045] A method for preparing a high-permeability puncture-resistant membrane material comprises the following steps:

[0046] Step 1: Mix PBAT, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:10:3, melt, extrude, and granulate at 155°C, repeat the melting, extrusion, and granulation process three times, and place in a 70°C oven to dry for 24 hours to obtain maleic anhydride grafted modified PBAT;

[0047] Step 2: Add the maleic anhydride grafted modified PBAT to chloroform, stir until dissolved, and dropwise add the amino-terminated liquid nitrile rubber. The mass ratio of maleic anhydride grafted modified PBAT, chloroform, and amino-terminated liquid nitrile rubber is 101.5:1200:25. The dropwise addition time of the amino-terminated liquid nitrile rubber is 1h. After the dropwise addition is completed, reflux reaction is carried out at 60°C for 2h. After the reaction is completed, add 5 times the mass of chloroform to precipitate deionized water, filter, take the filter cake, wash it three times with ethanol, and dry it in a vacuum oven at 60°C for 12h to obtain nitrile rubber modified PBAT;

[0048] Step 3, add the silicon-based mesoporous material to toluene, ultrasonically disperse it at a power of 300 W for 40 minutes, add γ-glycidyloxypropyltrimethoxysilane, the mass ratio of silicon-based mesoporous material, toluene, and γ-glycidyloxypropyltrimethoxysilane is 10:200:5, continue ultrasonication at a power of 300 W for 10 minutes, react at a temperature of 95°C for 5 hours, and after the reaction is completed, centrifuge, add toluene to the centrifugal precipitate, ultrasonically disperse it at a power of 300 W for 10 minutes, centrifuge, take the centrifugal precipitate, repeat the ultrasonic dispersion and centrifugation process six times, and place it in a vacuum oven at 60°C to dry for 12 hours to obtain an epoxy-modified silicon-based mesoporous material;

[0049] The nitrile rubber modified PBAT, the epoxy modified silicon-based mesoporous material, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecanol, and zinc stearate are mixed, and the mass ratio of the nitrile rubber modified PBAT, the epoxy modified silicon-based mesoporous material, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecanol, and zinc stearate is 100:5:1:1, and the mixture is melted at a melting temperature of 170° C. to obtain a modified PBAT melt;

[0050] Step 4: Extruding the modified PBAT melt at an extrusion die temperature of 175° C. and blowing the film to obtain a high permeability puncture-resistant film material;

[0051] The thickness of the high permeability puncture-resistant membrane material is 0.25 mm.

[0052] Example 3

[0053] A method for preparing a high-permeability puncture-resistant membrane material comprises the following steps:

[0054] Step 1: Mix PBAT, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:6:1.8, melt, extrude, and granulate at 145°C, repeat the melting, extrusion, and granulation process three times, and place in a 70°C oven to dry for 24 hours to obtain maleic anhydride grafted modified PBAT;

[0055] Step 2: Add the maleic anhydride grafted modified PBAT to chloroform, stir until dissolved, and add amino-terminated liquid nitrile rubber dropwise. The mass ratio of maleic anhydride grafted modified PBAT, chloroform, and amino-terminated liquid nitrile rubber is 100.7:1040:17.5. The dropwise addition time of the amino-terminated liquid nitrile rubber is 30 minutes. After the dropwise addition is completed, reflux reaction is carried out at 55°C for 2.5 hours. After the reaction is completed, 5 times the mass of chloroform is added for precipitation, filtration is performed, the filter cake is taken, washed three times with ethanol, and dried in a vacuum oven at 60°C for 12 hours to obtain nitrile rubber modified PBAT;

[0056] Step 3, add the silicon-based mesoporous material to toluene, ultrasonically disperse it at a power of 300 W for 40 minutes, add γ-glycidyloxypropyltrimethoxysilane, the mass ratio of silicon-based mesoporous material, toluene, and γ-glycidyloxypropyltrimethoxysilane is 6:200:2.5, continue ultrasonication at a power of 300 W for 10 minutes, react at a temperature of 90°C for 8 hours, and after the reaction is completed, centrifuge, add toluene to the centrifugal precipitate, ultrasonically disperse it at a power of 300 W for 10 minutes, centrifuge, take the centrifugal precipitate, repeat the ultrasonic dispersion and centrifugation process six times, and place it in a vacuum oven at 60°C to dry for 12 hours to obtain an epoxy-modified silicon-based mesoporous material;

[0057] The nitrile rubber modified PBAT, epoxy modified silicon-based mesoporous material, triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate] and calcium stearate are mixed, and the mass ratio of the nitrile rubber modified PBAT, epoxy modified silicon-based mesoporous material, triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate] and calcium stearate is 100:3.5:0.6:0.6, and the mixture is melted at a melting temperature of 165° C. to obtain a modified PBAT melt;

[0058] Step 4: Extruding the modified PBAT melt at an extrusion die temperature of 170° C. and blowing the film to obtain a high permeability puncture-resistant film material;

[0059] The thickness of the high permeability puncture-resistant membrane material is 0.25 mm.

[0060] Example 4

[0061] A method for preparing a high-permeability puncture-resistant membrane material comprises the following steps:

[0062] Step 1: Mix PBAT, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:7:2.1, melt, extrude, and granulate at 145°C, repeat the melting, extrusion, and granulation process three times, and place in a 70°C oven to dry for 24 hours to obtain maleic anhydride grafted modified PBAT;

[0063] Step 2: Add the maleic anhydride grafted modified PBAT to chloroform, stir until dissolved, and add amino-terminated liquid nitrile rubber dropwise. The mass ratio of maleic anhydride grafted modified PBAT, chloroform, and amino-terminated liquid nitrile rubber is 100.9:1080:20. The dropwise addition time of the amino-terminated liquid nitrile rubber is 30 minutes. After the dropwise addition is completed, reflux reaction is carried out at 55°C for 2.5 hours. After the reaction is completed, 5 times the mass of chloroform is added for precipitation, filtered, and the filter cake is taken. It is washed three times with ethanol and placed in a vacuum oven at 60°C for 12 hours to obtain nitrile rubber modified PBAT;

[0064] Step 3, add the silicon-based mesoporous material to toluene, ultrasonically disperse it at a power of 300 W for 40 minutes, add γ-glycidyloxypropyltrimethoxysilane, the mass ratio of silicon-based mesoporous material, toluene, and γ-glycidyloxypropyltrimethoxysilane is 7:200:3, continue ultrasonication at a power of 300 W for 10 minutes, react at a temperature of 90°C for 8 hours, and after the reaction is completed, centrifuge, add toluene to the centrifugal precipitate, ultrasonically disperse it at a power of 300 W for 10 minutes, centrifuge, take the centrifugal precipitate, repeat the ultrasonic dispersion and centrifugation process six times, and place it in a vacuum oven at 60°C to dry for 12 hours to obtain an epoxy-modified silicon-based mesoporous material;

[0065] The nitrile rubber modified PBAT, the epoxy modified silicon-based mesoporous material, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, and zinc stearate are mixed, and the mass ratio of the nitrile rubber modified PBAT, the epoxy modified silicon-based mesoporous material, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, and zinc stearate is 100:4:0.7:0.7, and the mixture is melted at a melting temperature of 165° C. to obtain a modified PBAT melt;

[0066] Step 4: Extruding the modified PBAT melt at an extrusion die temperature of 170° C. and blowing the film to obtain a high permeability puncture-resistant film material;

[0067] The thickness of the high permeability puncture-resistant membrane material is 0.25 mm.

[0068] Example 5

[0069] A method for preparing a high-permeability puncture-resistant membrane material comprises the following steps:

[0070] Step 1: Mix PBAT, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:8:2.4, melt, extrude, and granulate at 145°C, repeat the melting, extrusion, and granulation process three times, and place in a 70°C oven to dry for 24 hours to obtain maleic anhydride grafted modified PBAT;

[0071] Step 2, add the maleic anhydride grafted modified PBAT to chloroform, stir until dissolved, add amino-terminated liquid nitrile rubber dropwise, the mass ratio of maleic anhydride grafted modified PBAT, chloroform, and amino-terminated liquid nitrile rubber is 101.1:1120:20, and the amino-terminated liquid nitrile rubber is added for 30 minutes. After the addition is completed, reflux at 55°C for 2.5 hours. After the reaction is completed, add 5 times the mass of chloroform to precipitate deionized water, filter, take the filter cake, wash it three times with ethanol, and place it in a vacuum oven at 60°C for 12 hours to obtain nitrile rubber modified PBAT;

[0072] Step 3, add the silicon-based mesoporous material to toluene, ultrasonically disperse it at a power of 300 W for 40 minutes, add γ-glycidyloxypropyltrimethoxysilane, the mass ratio of silicon-based mesoporous material, toluene, and γ-glycidyloxypropyltrimethoxysilane is 8:200:4, continue ultrasonication at a power of 300 W for 10 minutes, react at a temperature of 90° C. for 8 hours, centrifuge after the reaction, add toluene to the centrifugal precipitate, ultrasonically disperse it at a power of 300 W for 10 minutes, centrifuge, take the centrifugal precipitate, repeat the ultrasonic dispersion and centrifugation process six times, place it in a vacuum oven at 60° C. and dry it for 12 hours to obtain the epoxy-modified silicon-based mesoporous material;

[0073] The nitrile rubber modified PBAT, the epoxy modified silicon-based mesoporous material, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, and zinc stearate are mixed, and the mass ratio of the nitrile rubber modified PBAT, the epoxy modified silicon-based mesoporous material, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, and zinc stearate is 100:4:0.8:0.8, and the mixture is melted at a melting temperature of 165° C. to obtain a modified PBAT melt;

[0074] Step 4: Extruding the modified PBAT melt at an extrusion die temperature of 170° C. and blowing the film to obtain a high permeability puncture-resistant film material;

[0075] The thickness of the high permeability puncture-resistant membrane material is 0.25 mm.

[0076] Example 6

[0077] A method for preparing a high-permeability puncture-resistant membrane material comprises the following steps:

[0078] Step 1: Mix PBAT, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:9:2.7, melt, extrude, and granulate at 145°C, repeat the melting, extrusion, and granulation process three times, and place in a 70°C oven to dry for 24 hours to obtain maleic anhydride grafted modified PBAT;

[0079] Step 2: Add the maleic anhydride grafted modified PBAT to chloroform, stir until dissolved, and add amino-terminated liquid nitrile rubber dropwise. The mass ratio of maleic anhydride grafted modified PBAT, chloroform, and amino-terminated liquid nitrile rubber is 101.3:1160:22.5. The dropwise addition time of the amino-terminated liquid nitrile rubber is 30 minutes. After the dropwise addition is completed, reflux reaction is carried out at 55°C for 2.5 hours. After the reaction is completed, 5 times the mass of chloroform is added for precipitation, filtered, and the filter cake is taken. It is washed three times with ethanol and placed in a vacuum oven at 60°C for 12 hours to obtain nitrile rubber modified PBAT;

[0080] Step 3, add the silicon-based mesoporous material to toluene, ultrasonically disperse it at a power of 300 W for 40 minutes, add γ-glycidyloxypropyltrimethoxysilane, the mass ratio of silicon-based mesoporous material, toluene, and γ-glycidyloxypropyltrimethoxysilane is 9:200:4.5, continue ultrasonication at a power of 300 W for 10 minutes, react at a temperature of 90°C for 8 hours, and after the reaction is completed, centrifuge, add toluene to the centrifugal precipitate, ultrasonically disperse it at a power of 300 W for 10 minutes, centrifuge, take the centrifugal precipitate, repeat the ultrasonic dispersion and centrifugation process six times, and place it in a vacuum oven at 60°C to dry for 12 hours to obtain an epoxy-modified silicon-based mesoporous material;

[0081] The nitrile rubber modified PBAT, epoxy modified silicon-based mesoporous material, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester and zinc stearate are mixed, and the mass ratio of the nitrile rubber modified PBAT, epoxy modified silicon-based mesoporous material, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester and zinc stearate is 100:4.5:0.9:0.9, and the mixture is melted at a melting temperature of 165° C. to obtain a modified PBAT melt;

[0082] Step 4: Extruding the modified PBAT melt at an extrusion die temperature of 170° C. and blowing the film to obtain a high permeability puncture-resistant film material;

[0083] The thickness of the high permeability puncture-resistant membrane material is 0.25 mm.

[0084] Comparative Example 1

[0085] A method for preparing a high-permeability puncture-resistant membrane material comprises the following steps:

[0086] Step 1: Mix PBAT, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:5:1.5, melt, extrude, and granulate at 135°C, repeat the melting, extrusion, and granulation process three times, and place in a 70°C oven to dry for 24 hours to obtain maleic anhydride grafted modified PBAT;

[0087] Step 2: Add the maleic anhydride grafted modified PBAT to chloroform, stir until dissolved, and add amino-terminated liquid nitrile rubber dropwise. The mass ratio of maleic anhydride grafted modified PBAT, chloroform, and amino-terminated liquid nitrile rubber is 100.5:1000:30. The dropwise addition time of the amino-terminated liquid nitrile rubber is 30 minutes. After the dropwise addition is completed, reflux at 50°C for 3 hours. After the reaction is completed, add 5 times the mass of chloroform to precipitate deionized water, filter, take the filter cake, wash it three times with ethanol, and dry it in a vacuum oven at 60°C for 12 hours to obtain nitrile rubber modified PBAT;

[0088] Step 3, mixing nitrile rubber modified PBAT, silicon-based mesoporous material, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and calcium stearate, wherein the mass ratio of nitrile rubber modified PBAT, silicon-based mesoporous material, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and calcium stearate is 100:2.8:0.5:0.5, and melting, the melting temperature is 160° C., to obtain a modified PBAT melt;

[0089] Step 4: Extruding the modified PBAT melt at an extrusion die temperature of 165° C. and blowing the film to obtain a high permeability puncture-resistant film material;

[0090] The thickness of the high permeability puncture-resistant membrane material is 0.25 mm.

[0091] Comparative Example 2

[0092] A method for preparing a high-permeability puncture-resistant membrane material comprises the following steps:

[0093] Step 1, PBAT, amino-terminated liquid nitrile rubber, silicon-based mesoporous material, tetrakis [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, and calcium stearate are mixed, and the mass ratio of PBAT, amino-terminated liquid nitrile rubber, silicon-based mesoporous material, tetrakis [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, and calcium stearate is 90:10:2.8:0.5:0.5, and the mixture is melted at a melting temperature of 160° C. to obtain a modified PBAT melt;

[0094] Step 4: Extruding the modified PBAT melt at an extrusion die temperature of 165° C. and blowing the film to obtain a high permeability puncture-resistant film material;

[0095] The thickness of the high permeability puncture-resistant membrane material is 0.25 mm.

[0096] Comparative Example 3

[0097] A method for preparing a high-permeability puncture-resistant membrane material comprises the following steps:

[0098] Step 1: Mix PBAT, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:5:1.5, melt, extrude, and granulate at 135°C, repeat the melting, extrusion, and granulation process three times, and place in a 70°C oven to dry for 24 hours to obtain maleic anhydride grafted modified PBAT;

[0099] Step 2: Add the maleic anhydride grafted modified PBAT to chloroform, stir until dissolved, and add amino-terminated liquid nitrile rubber dropwise. The mass ratio of maleic anhydride grafted modified PBAT, chloroform, and amino-terminated liquid nitrile rubber is 100.5:1000:50. The dropwise addition time of the amino-terminated liquid nitrile rubber is 30 minutes. After the dropwise addition is completed, reflux at 50°C for 3 hours. After the reaction is completed, add 5 times the mass of chloroform to precipitate deionized water, filter, take the filter cake, wash it three times with ethanol, and dry it in a vacuum oven at 60°C for 12 hours to obtain nitrile rubber modified PBAT;

[0100] Step 3, mixing nitrile rubber modified PBAT, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and calcium stearate, wherein the mass ratio of nitrile rubber modified PBAT, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and calcium stearate is 102.8:0.5:0.5, and melting, and the melting temperature is 160° C. to obtain a modified PBAT melt;

[0101] Step 4: Extruding the modified PBAT melt at an extrusion die temperature of 165° C. and blowing the film to obtain a high permeability puncture-resistant film material;

[0102] The thickness of the high permeability puncture-resistant membrane material is 0.25 mm.

[0103] In the above embodiments and comparative examples, PBAT was purchased from Xinjiang Blue Mountain Tunhe Chemical Co., Ltd., model: TH801T, melting temperature: 110-120°C, tensile stress: 20-25MPa; amino-terminated liquid nitrile rubber was purchased from Jingjiang Tonggao Chemical Co., Ltd., with an effective substance content of 99.5% and an average molecular weight of 10,000; the silicon-based mesoporous material was mesoporous silica MCM-41, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with a pore size of 3-5nm.

[0104] Test example

[0105] The performance tests were performed on the membrane materials prepared in Examples 1-6 and Comparative Examples 1-3:

[0106] (1) Permeability test: The oxygen (O2), carbon dioxide (CO2) and water vapor permeability of the membrane material was tested. The test methods of O2 permeability and CO2 permeability refer to the standard GB / T1038.1-2022 "Plastic film and sheet gas permeability test method Part 1: Pressure difference method". The membrane material was cut into 150 mm × 95 mm samples and the O2 permeability and CO2 permeability of the membrane material were tested using a GTR-701M gas permeability tester in an environment with a temperature of 23 ° C and a humidity of 50 ± 5%. The permeation area was 40 cm 2The test method of water vapor permeability refers to the standard GB / T1037-2021 "Cup weight gain and weight loss method for water vapor permeability of plastic films and sheets". The film material is cut into a circular sample with a diameter of 6.5 cm. The sample is covered on the mouth of the moisture permeable cup and sealed with molten sealing wax. The moisture permeable cup is placed in a constant temperature and humidity chamber with a temperature of 23±0.6℃ and a humidity of 90±2%. The water vapor permeability is calculated according to the mass of the moisture permeable cup before and after the test. The test results of O2 permeability, CO2 permeability and water vapor permeability are shown in Table 1:

[0107] Table 1

[0108]

[0109]

[0110] As can be seen from Table 1, the membrane material prepared by the present invention has good permeability. The PBAT-based membrane material has good water vapor permeability, good adsorption and diffusion of CO2, and high CO2 gas permeability; the inorganic toughening material silicon-based mesoporous material introduced has a porous structure, which makes the membrane material have a small permeation resistance to gas, is conducive to gas diffusion and transmission, and can effectively improve the permeability of the membrane material. Compared with Example 1, in Comparative Example 1, the silicon-based mesoporous material has not been subjected to epoxy modification treatment, and its compatibility with the PBAT resin and its uniformity of dispersion in the PBAT resin are reduced, and the permeability of the membrane material is reduced; in Comparative Example 2, the silicon-based mesoporous material has not been subjected to epoxy modification treatment, and its compatibility with the PBAT resin and its uniformity of dispersion in the PBAT resin are reduced, resulting in reduced permeability of the membrane material, and the amino-terminated liquid nitrile rubber is not chemically bonded to the PBAT molecule, which mainly affects the puncture resistance of the membrane material and has no significant effect on the permeability of the membrane material. The permeability of the membrane material is equivalent to that of Comparative Example 1; in Comparative Example 3, no silicon-based mesoporous material is added, which has the most significant effect on the permeability of the membrane material and has the worst permeability.

[0111] (2) Puncture resistance test: The puncture resistance of the film material is tested. The test method refers to the standard GB / T37841-2019 "Test method for puncture resistance of plastic film and sheet". The test results are shown in Table 2:

[0112] Table 2

[0113]

[0114] As can be seen from Table 2, the membrane material prepared by the present invention has good puncture resistance. The introduction of organic toughening materials of nitrile rubber and inorganic toughening materials of silicon-based mesoporous materials can effectively provide toughness of the membrane material, thereby improving the puncture resistance of the membrane material. Compared with Example 1, in Comparative Example 1, the silicon-based mesoporous material has not undergone epoxy modification, and its compatibility with the PBAT resin and its uniformity of dispersion in the PBAT resin have decreased, and the puncture resistance of the membrane material has decreased; in Comparative Example 2, the silicon-based mesoporous material has also not undergone epoxy modification, and its compatibility with the PBAT resin and its uniformity of dispersion in the PBAT resin have decreased, and the amino-terminated liquid nitrile rubber has no chemical bond to the PBAT molecule, and the puncture resistance of the membrane material has further decreased; in Comparative Example 3, no silicon-based mesoporous material is added, which has the most significant effect on the permeability of the membrane material and the worst puncture resistance.

[0115] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high permeability puncture-resistant membrane material, characterized in that: The following steps are involved: Step 1: adding maleic anhydride grafted modified PBAT into chloroform, stirring until dissolved, adding amino-terminated liquid nitrile rubber dropwise, reacting after the addition is complete, precipitating, filtering, washing, and drying to obtain nitrile rubber modified PBAT; Step 2: adding the silicon-based mesoporous material to toluene, and after ultrasonic dispersion, adding γ-glycidyloxypropyltrimethoxysilane, continuing ultrasonication, reacting, and after the reaction is completed, centrifuging, purifying, and drying to obtain the epoxy-modified silicon-based mesoporous material; The nitrile rubber modified PBAT, the epoxy modified silicon-based mesoporous material, the antioxidant and the lubricant are mixed and melted to obtain a modified PBAT melt; Step 3: Extrude the modified PBAT melt and blow the film to obtain a high permeability and puncture-resistant film material.

2. The method for preparing a high permeability puncture-resistant membrane material according to claim 1, characterized in that: The maleic anhydride grafted modified PBAT used in step 1 is prepared by the following steps: PBAT, maleic anhydride, and initiator dicumyl peroxide are mixed, melted, extruded, and granulated. The melting, extrusion, and granulation process are repeated three times, and dried to obtain maleic anhydride grafted modified PBAT.

3. The method for preparing a high permeability puncture-resistant membrane material according to claim 2, characterized in that: The mass ratio of the PBAT, maleic anhydride and initiator dicumyl peroxide is 100:(5-10):(1.5-3); the melting temperature is 135-155°C.

4. The method for preparing a high permeability puncture-resistant membrane material according to claim 1, characterized in that: In the step 1, the mass ratio of maleic anhydride grafted modified PBAT, chloroform, and amino-terminated liquid nitrile rubber is (100.5-101.5):(1000-1200):(15-25), and the reaction conditions are reflux reaction at a temperature of 50-60° C. for 2-3 hours.

5. The method for preparing a high permeability puncture-resistant membrane material according to claim 1, characterized in that: In the step 2, when preparing the epoxy-modified silicon-based mesoporous material, the mass ratio of the silicon-based mesoporous material, toluene, and γ-glycidyloxypropyltrimethoxysilane is (5-10):200:(2-5), and the reaction conditions are 85-95° C. for 5-10 hours.

6. The method for preparing a high permeability puncture-resistant membrane material according to claim 1, characterized in that: In the step 2, when preparing the modified PBAT melt, the mass ratio of the nitrile rubber modified PBAT, the epoxy modified silicon-based mesoporous material, the antioxidant, and the lubricant is 100:(3-5):(0.5-1):(0.5-1), and the melting temperature is 160-170°C.

7. The method for preparing a high permeability puncture-resistant membrane material according to claim 1, characterized in that: In the step 2, the antioxidant includes any one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, n-octadecanol β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate], and the lubricant includes any one of calcium stearate and zinc stearate.

8. The method for preparing a high-permeability puncture-resistant membrane material according to claim 1, characterized in that: In the step 3, the extrusion die temperature is 165-175°C.

9. A high permeability puncture-resistant film material prepared by the method for preparing a high permeability puncture-resistant film material according to any one of claims 1 to 8.

10. Use of the high permeability puncture-resistant membrane material according to claim 9 in rice planting.

Citation Information

Patent Citations

  • A method for preparing a carbon membrane with high gas permeability

    CN107469640B

  • Preparation process of antibacterial and puncture-resistant PBAT composite film

    CN115558139B

  • Biodegradable toughened high-temperature-resistant composite straw

    CN114103274A

  • Method for preparing high-tensile PBAT (poly (butylene adipate-co-terephthalate)) resin by supercritical method

    CN116285246A

  • Antibacterial PLA-based degradable polymer material, preparation method and application of antibacterial PLA-based degradable polymer material in emulsion pump head

    CN117777692A